The relationship between insight and affective temperament in bipolar disorder: an exploratory study - Silva,Rafael de Assis da (2018)
Abstract Introduction In recent years, the association between temperament and clinical characteristics of mood disorders has been studied. Most bipolar patients show deficits in their awareness of signs and symptoms. The relationship between affective temperament and insight in bipolar patients has not been carried out in the literature so far. Objective To evaluate the relationship between affective temperament and insight in bipolar disorder. Method A group of 65 bipolar patients were followed during a year. Patients underwent a clinical assessment and were diagnosed using criteria from the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5). Insight was evaluated through the Insight Scale for Affective Disorders (ISAD), and affective temperament, through the TEMPS-Rio de Janeiro. The relationship between affective temperament and insight was explored with Spearman rho correlations between scores on each item of the ISAD and on the TEMPS-Rio de Janeiro subscales. Results In euthymic phases, bipolars with depressive temperament were associated with a higher level of insight about the consequences of the disorder; when in mania, patients showed better insight about having an affective disorder, presenting psychomotor alterations, and suffering from guilt or grandiosity. Similarly, bipolar patients with higher scores of anxious temperament, when in mania, had better insight on alterations in attention. Bipolar patients with higher scores of hyperthymic temperament, when in mania, showed the worst insight about thought disorder. Conclusion In addition to being determined by the phase of the disease and several varying symptoms, the level of insight in bipolar patients is also influenced by affective temperament.